Analisis Penerapan Customer Relationship Management Pada Instansi Pemerintah (Studi Kasus: Badan Pusat Statistik) - Pertiwi, Ratih Putri; Wisnubroto, Agus Sigit; Yudhianto, Riswan Haryo; Prasetya, Roliand; Hidayanto, Achmad Nizar (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2023)
Many companies implement Customer Relationship Management (CRM) with the aim of building good relationships with customers to increase sales and business competitiveness. Similar to businesses, the concept of CRM can also be applied to government agencies that provide public services to the community, which is also known as Citizenship Relationship Management (CiRM/CzRM). Statistics Indonesia (BPS), as a non-ministerial government agency with the function of administering national statistics, began implementing CRM in 2010 with the establishment of the Statistical Service Information System (SILASTIK). The services included in SILASTIK are consulting services and requests for data/statistics. To increase the trust of various segments of society as data consumers of BPS, SILASTIK is continuously developed from year to year through stages into an Integrated Statistical Service (PST) that integrates various types of services that were previously silos/spread across several BPS work units. This research analyzes aspects of CRM in government agencies based on literature and its implementation process within the organization by taking case study of the SILASTIK. Data collection was carried out using the triangulation method (interviews, observations, and document analysis). The analysis was carried out by studying the CRM aspects of SILASTIK. Recommendations are given based on the results of the analysis so that they can provide an overview to practitioners and academics regarding the implementation of CRM through the development of information systems. In addition, this research contributes to providing examples of case studies of the implementation of CRM in the field of public services by government agencies for future development and research.